Pendampingan Business Model Canvas dan Google My Business Kepada Malijo Coffee Shop - William Wendy Ary (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
Micro, Small and Medium Enterprises (MSMEs) are activities that are closely related to today's daily life, especially in the all-digital era. Based on data from the Indonesian Central Statistics Agency (BPS), Indonesian MSMEs have contributed 60.3% of Indonesia's total Gross Domestic Product (GDP). However, only 13% of the total MSMEs make good use of technological advances. One of the MSMEs that have not used the digital era as an opportunity is the Malijo Coffee Shop (MCS). The purpose of this community service activity for MCS is to provide knowledge and maximize the potential of the coffee shop business by using the Business Model Canvas approach and the internet-based supporting application Google My Business. The methods applied in the service to MCS are lectures, tutorials, and practices. The result of this service is an increase in the understanding of MCS owners on the implementation of business strategies through BMC and Google My Business assistance and an increase in the number of visitors compared to before and after the implementation of this assistance.